Spreading of Alzheimer’s disease inflammatory signaling through soluble micro-RNA - Lukiw, Walter J. (Neuroreport, 2012)
Alzheimer’s disease is a progressive, neurodegenerative disorder that develops within the limbic system, spreading radially into anatomically linked brain association areas as the disease progresses. Analysis of temporal-lobe association of neocortex-derived extracellular fluid and cerebrospinal fluid from Alzheimer’s disease patients shows an abundant presence of micro-RNA (miRNA), including the proinflammatory miRNA-146a and miRNA-155. Using a novel and highly sensitive LED-Northern dot-blot focusing technique, we detected the secretion of potentially pathogenic amounts of miRNA-146a and miRNA-155 from stressed human primary neural cells. A conditioned medium containing miRNA-146a and miRNA-155 was found to induce Alzheimer-type gene expression changes in control brain cells. These included downregulation in the expression of an important repressor of the innate immune response, complement factor H (CFH). These effects were neutralized using anti-miRNA strategies. Anti-miRNA-based therapeutics may provide a novel and efficacious treatment to stem the miRNA-mediated spreading of inflammatory signaling involved in Alzheimer’s disease.